Uncovering The Pharmacological Mechanism of Ficus elastica as Anti-hyperlipidemia Candidate: LC-HRMS, Network Pharmacology, In vitro and In vivo Studies - Gita Susanti; Yufri Aldi; Dian Handayani; Friardi Ismed; Arif Setiawansyah (Journal of Multidisciplinary Applied Natural Science, 2025)
Hyperlipidemia is a major risk factor for cardiovascular diseases. While conventional treatments exist, there is a growing interest in natural remedies with fewer side effects. Ficus elastica has promising medicinal properties, yet its potential as an anti-hyperlipidemic agent remains unexplored. This study aimed to investigate the anti-hyperlipidemic effects of F. elastica using an integrated approach of LC-HRMS-based chemical bioinformatics and in vitro/in vivo experimental validation. The anti-hyperlipidemic potential of F. elastica and its mechanism of action were screened using integrative computational network pharmacology followed by in vitro HMG-CoA reductase inhibition and in vivo lipid-lowering activity in a hyperlipidemia rat model. Network pharmacology analysis identified STAT3, HSP90AA1, and TLR4 as potential core targets involved in lipid and atherosclerosis-related KEGG pathways. Molecular docking simulations revealed high-affinity interactions between F. elastica compounds and the identified targets, notably compound 41 and compound 61. In vitro assay demonstrated that ethanolic extract of F. elastica inhibited HMG-CoA reductase with an IC50 of 297.73 µg/mL. In vivo experiment using a hyperlipidemic rat model showed significant reductions in total cholesterol, triglycerides, and increased HDL levels. The reduction of triglycerides and elevation of HDL level after F. elastica ethanolic extract supplementation is similar to the effect from supplementation of simvastatin. These findings suggest that F. elastica ethanolic extract possesses notable anti-hyperlipidemic properties, likely mediated through multiple molecular targets and pathways. The study highlights the potential of F. elastica ethanolic extract as a promising candidate for anti-hyperlipidemic therapy and underscores the efficacy of integrating computational and experimental approaches in natural product research.